Transient Elastography for Spleen Stiffness Measurement in Patients With Cirrhosis: Role in Degree of Thrombocytopenia. (1st July 2016) - Chien, Cheng-Hung; Lin, Yi-Lan; Chien, Rong-Nan; Hu, Ching-Chih; Yen, Cho-Li; Lee, Tsung-Shih; Hsieh, Po-Jen; Lin, Chih-Lang
Abstract : Objectives: The purpose of our study was to evaluate the relationship between spleen stiffness measured by transient elastography and the degree of thrombocytopenia in patients with liver cirrhosis. Methods: A total of 67 patients with liver cirrhosis were prospectively enrolled in the study. All patients underwent single‐day hematologic and biochemical tests, sonography, and transient elastography of the liver and spleen. Thrombocytopenia was categorized as mild (platelet count, 75, 000–150, 000/μL), moderate (50, 000–75, 000/μL), and severe (<50, 000/μL). Results: The degree of thrombocytopenia was significantly correlated with spleen stiffness ( P = .001) and spleen size ( P = .002) but not with liver stiffness ( P = .086). In patients without splenomegaly, spleen stiffness values were significantly higher in patients with thrombocytopenia than in those without thrombocytopenia ( P = .035). In patients with splenomegaly, spleen stiffness values were significantly higher in patients with moderate to severe thrombocytopenia than in those with a normal platelet count or mild thrombocytopenia ( P = .007). Compared to liver stiffness, spleen stiffness showed a better and statistically significant correlation with platelet count and spleen size in patients with cirrhosis. Conclusions: The degree of thrombocytopenia was directly correlated with spleen stiffness, irrespective of the presence of splenomegaly. The clinical phenomenon of unexpected thrombocytopenia may be explained by a subtle or irreversible change in spleen stiffness.